Stability and deformation analysis of embankment on soft clay by using limit equilibrium method and finite element method - Nik Adly Akmal Ahmad (School of Environmental Engineering, University Malaysia Perlis, 2016)
This study is about the deformation and stability of embankment on soft clay. The problem of an embankment on soft clay was seepage water in embankment, toe drain, height of embankment, base slope inclination, soil compaction and fill materials on the seismic behaviour of embankment that make embankment collapse. To analyse the deformation and stability of embankment, bore log analysis is required. For this study, soil profile is determined that is soft clay. After the soil profile was determined, start the modelling for embankment. Soil parameter was used to make the modelling of embankment. Soil parameter data were collected and combined. For the deformation of embankment, was done by finite element method (FEM) by using PLAXIS software. By using this software, the displacement will shows the deformation of the embankment. There will be failure of embankment because the total of displacement was too high. For the stability of the embankment, was done by limit equilibrium method (LEM) based on factor of safety by using SLOPE/W software. This software will calculate the factor of safety. Factor of safety will effect the stability of the embankment. When factor of safety is small, the stabililty of embankment not stable and cause failure of embankment. For the conclusion, good deformation and stability of embankment will effect the embankment.